2010
DOI: 10.3109/09546631003762654
|View full text |Cite
|
Sign up to set email alerts
|

Liquid nitrogen cryotherapy on Leishmania donovani cutaneous leishmaniasis

Abstract: LN (77.15% cure within one to four cryosessions) is an alternative to intralesional sodium stibogluconate in the treatment of papules measuring ≤ 1 cm. In type V skin, LN should be avoided on the face, and on patients who have a tendency to form keloids. We recommend giving cryotherapy using cryoguns (instead of cotton swabs attached to ekels) fortnightly (not weekly), which may minimize ulceration, and therefore scarring.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
25
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 15 publications
0
25
0
Order By: Relevance
“…Until recent years, this has been a neglected disease locally and was thought to be a disease of military personnel (6,7). Recent literature (10,11,13,14) showed that this was a disease of locals, where farmers and children who engaged in outdoor activities were the mostly affected. With increased case finding and identification of this disease, it became an important public health problem.…”
Section: Introductionmentioning
confidence: 99%
“…Until recent years, this has been a neglected disease locally and was thought to be a disease of military personnel (6,7). Recent literature (10,11,13,14) showed that this was a disease of locals, where farmers and children who engaged in outdoor activities were the mostly affected. With increased case finding and identification of this disease, it became an important public health problem.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, treatment must be non‐toxic and must result in a cosmetic appearance superior to that of natural healing. During the period of the present study, intralesional sodium stibogluconate (SSG) and liquid nitrogen cryotherapy were widely used as therapies for CL in Sri Lanka.…”
Section: Introductionmentioning
confidence: 99%
“…It causes mild and transient side effects (pain, hypopigmentation) and has excellent cosmetic results, which was confirmed by our observation. [9][10][11][12]…”
Section: Therapeutic Aspectmentioning
confidence: 99%